Immune-mediated rippling muscle disease with myasthenia gravis: a report of seven patients with long-term follow-up in two. - Schoser, B; Jacob, S; Hilton-Jones, D; Müller-Felber, W; Kubisch, C; Claus, D; Goebel, H; Vita, G; Vincent, A; Toscano, A; Van den Bergh, P (2009)
We report seven patients with immune-mediated rippling muscle disease (iRMD) and AChR-antibody positive myasthenia gravis (MG) without germline caveolin-3 gene mutations. We describe the follow-up of two patients and the clinical features of five new patients (1 female, 4 male, aged 32 to 69 years). These presented with significant generalized, exercise-induced and electrically-silent muscle rippling with myalgia, combined with generalized MG. In two of the seven patients, MG appeared before iRMD. Mediastinal imaging excluded thymic alterations in all, although two had other coincident tumours. Myalgia and rippling were aggravated by acetylcholinesterase-inhibitor treatment. Generalized MG and iRMD were successfully treated with plasma exchange, steroids and azathioprine in the two patients followed long-term. Muscle morphology of five patients showed a minimal myopathic pattern with rare lymphohistiocytic infiltration. In four patients, sarcolemmal caveolin-3, and dysferlin immunofluorescence staining was moderately reduced in a mosaic pattern, but caveolin-3 protein on Western blots was clearly reduced only in two. Notably, electron microscopy showed that caveolae were almost completely lost at the sarcolemma in the three biopsies examined but not in endothelium. Antibodies targeting high molecular weight muscle proteins, likely associated with the neuromuscular endplate and sarcolemma, were found in the iRMD patients but also in age-matched MG patients without iRMD. Since the generalized MG and iRMD improved with immunosuppressive treatments, it is likely that both are caused by autoantibodies, but the target for pathogenic antibodies in iRMD requires further study.